A Click Approach to Novel D-Ring-Substituted 16α-Triazolylestrone Derivatives and Characterization of Their Antiproliferative Properties - Molnár, Judit; Frank, Éva; Minorics, Renáta; Kádár, Zalán; Ocsovszki, Imre; Schönecker, Bruno; Wölfling, János; Zupkó, István (PLOS ONE, 2015)
A simple and efficient synthesis of novel, D-ring substituted estrone derivatives containing a 16α-triazolyl moiety is described. Two epimeric azido alcohols (16α-azido-17α-hydroxy and 16α-azido-17β-hydroxy) of estra-1,3,5(10)-triene-3-methyl ether were prepared, followed by copper(I)-catalyzed azide-alkyne cycloaddition with various terminal alkynes. The steroidal triazoles were obtained in high yields and their activities against three human cancer cell lines (HeLa, MCF7 and A431) were screened. The most effective analogs were submitted to additional experiments in order to characterize their antiproliferative properties. As evidenced by flow cytometry, the selected steroids induced a disturbance in the HeLa cell cycle in a concentration- and exposure-dependent manner, through an increase of the hypodiploid population (subG1) and a cell cycle arrest in the G2/M phase. A noncancerous human fibroblast cell line (MRC5) was used to determine the selectivities of these compounds. Fluorescent microscopy after Hoechst 33258 - propidium iodide (HOPI) double staining revealed nuclear condensation and disturbed cell membrane integrity. The enhanced activities of caspase-3 and caspase-9 without activation of caspase-8 in the treated cells indicated the activation of the intrinsic pathway of apoptosis. The levels of cell cycle regulators (CDK1, cyclin B1/B2 and cdc25B) were decreased and the ratio Bax/Bcl-2 was increased 24 h after the treatment of HeLa cells (determined at an mRNA level by means of an RT-PCR technique). Under the same conditions, two agents elicited substantially increased degrees of phosphorylation of stathmin, as evidenced by Western blotting. The presented results demonstrate that these steroids can be regarded as appropriate structural scaffolds for the design and synthesis of further steroid analogs as innovative drug candidates with good efficacy.